Self-Employed Finance in the New Russian Economy - T. V. Zhukova; Y. M. Mirkin (Мир новой экономики)
We based our study on statistical, actuarial, and predictive methods, including the method of moving ages. We assessed qualitatively and quantitatively Russian self-employed. Their potential for participation in pension insurance is assessed using foreign experience. We proposed promising instruments for pensions of self-employed. We concretized the concept of self-employed for the Russian pension system based on international approaches. Their number, gender, age and professional composition and income level are estimated, including international comparison. Further, we predicted the demographic number of self-employed as potential recipients of social pensions. Their income potential for pension insurance is assessed. Finally, we developed recommendations for using the best foreign experience to expand the coverage of self-employed with pension insurance.